مسح التطورات الاقتصادية والاجتماعية في منطقة الإسكوا 2011-2012 - United Nations Economic; Social Commission for Western Asia (United Nations, 2013)
The Survey of Economic and Social Development in the Arab Region 2011-2012 assesses the most recent economic and social developments in the Arab region, using the data that became available by the 2nd quarter of 2012. It found that GDP growth performance between major oil producers and the rest of the Arab region appeared to diverge. While GCC countries’ oil export revenues marked all-time high, the subdued intra-regional tourism, trade and foreign direct investment clearly failed to produce the positive spill-over of oil revenues over the Arab region. It emphasizes that this growth polarization deepens already uncertain prospects of the region’s economic and social development, noting that the unemployment rate of the Arab region remains at the highest level world-wide. The Survey concludes that the use of “regional leverage” by articulating regional cooperation frameworks for Arab regional integration is crucial to tackle pressing issues for a constructive economic and social transition of the region.